Review on solid-state transfer switch configurations and control methods: Applications, operations, issues, and future directions - Mollik M.S.; Hannan M.A.; Ker P.J.; Faisal M.; Rahman M.S.A.; Mansur M.; Lipu M.S.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Control systems; Electric power distribution; Electric power transmission; Electric switches; Topology; Comparative analysis; Control methods; Control operations; Crucial technology; Future performance; Future prospects; Power system engineers; Solid-state transfer switches; Electric power system control